Co-simulation of linear congruential generator by using Xilinx system generator and MATLAB Simulink - Suneeta Suneeta (Institute of Advanced Engineering and Science, 2021)
Arbitrary numerals are utilized in a wide range of uses. Genuine arbitrary numeral generators are moderate and costly for some applications while pseudo arbitrary numeral generators (RNG) do the trick for most applications. This paper fundamentally concentrates around the co-simulation of the linear congruential generator (LCG) model utilizing the Xilinx System generator and checking on Matlab Simulink. The design is obtained from the LCG calculation offered by Lehmer. Word lengths decrease strategy has been utilized to streamline the circuit. Simulation has been done effectively. The effective N bit LCG is structured and tried by utilizing demonstrating in MatLab Simulink. The Co-simulation of the model is done by utilizing the Xilinx system generator. This paper conducts an exhaustive search for the best arbitrary numeral generator in a full period linear congruential generator (LCG) with the largest prime numbers.